Vibration and noise suppression method of transformer. Issue 1 (1st January 2022) - Yu, XC; Zou, DP; Fan, MZ; Dong, X; Du, F
Abstract: Aiming at the problem of noise and vibration of distribution transformer body and base connector under heavy load, the corresponding relationship between vibration and noise, load and power factor of distribution transformer is studied in this paper. In order to improve the operation reliability of distribution transformer, a noise and vibration suppression method based on load scenario optimization is proposed. From the aspects of design reliability, data detection and noise level correction, the typical relationship between the increase of noise level and DC current, noise spectrum and DC bias noise is obtained, and the DC bias limiting measures and correction suggestions are given.